De la meilleure façon de constituer une collection. Le cas des émaux « byzantins » de Mikhaïl Botkine - Aglaé Achechova (Les Cahiers de l'École du Louvre)
The collection of supposedly “Byzantine” enamels belonging to Mikhail Petrovich Botkin (1839-1914) is a remarkable case in the history of collecting, particularly if one is interested in the collector’s motivation. The types of objects collected by Botkin changed as he travelled and with fashion: he successively collected the works of the painter A. Ivanov, European medieval and Renaissance objets d’art, and then medieval Russian art. Botkin’s acquisition methods, entirely devoid of scruples, were well-known during his lifetime. The core of his collection, comprised of 171 cloisonné enamels on gold, most of which were thought to have come from Georgia, was put together over about 25 years, with no trips to the Caucasus by Botkin being known. From the publication of the catalogue of this collection in 1911, doubts concerning the authenticity of the pieces were expressed: was it possible to collect such a great number of extremely rare objects in such a short period of time? A thorough investigation by the designer of the house of Fabergé, François Birbaum, enabled the secret workshop that had produced most of the enamels in Mikhail Botkin’s collection to be discovered in 1914. The reasons for a collector to put together, apparently with full knowledge of the facts, a collection of fakes may be many: the control of the quantity and the quality of the pieces he was collecting, the mastery of the competition of the elimination of the concerns usually encountered: the rarity and uncertain provenance of the objects.